DYNAMICS OF THE IMPLEMENTATION OF THE FREE NUTRITIOUS MEAL PROGRAM IN NORTH SULAWESI: AN ANALYSIS OF MULTISECTORAL COMPLEXITY, LOGISTICAL CHALLENGES, AND SUSTAINABILITY STRATEGIES - Franky R.D Rengkung; Johny Peter Lengkong; Efvendi R. Sondak; Zainul Abidin (RADJA PUBLIKA, 2026)
The Free Nutritious Meal Program (PMBG) is a national strategic policy designed to improve the quality of human resources by fulfilling the nutritional needs of schoolchildren, toddlers, and pregnant women as part of the Indonesia Golden 2045 agenda. However, the implementation of the program in North Sulawesi Province faces considerable complexity due to its archipelagic geographical characteristics, limited logistics infrastructure, multisectoral coordination, and challenges related to sustainable financing. This study aims to analyze the implementation dynamics of the PMBG in North Sulawesi by examining the complexity of intersectoral collaboration, food distribution constraints, and strategies to ensure program sustainability. The study employed a qualitative-descriptive approach using a regional case study design. Data were collected through the analysis of policy documents, government reports, statistical data, and a systematic literature review, and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the successful implementation of the PMBG is strongly influenced by the integration of micro-level beneficiary data, strengthened cross-sectoral coordination, the optimization of local food as the primary supply chain resource, the development of a hub-and-spoke distribution model, and the enhancement of cold-chain infrastructure across archipelagic areas. Furthermore, program sustainability requires the diversification of funding sources, the digitalization of procurement and monitoring systems, strengthened food safety measures, culturally based nutrition education, and active community participation in program governance. This study confirms that the implementation of the PMBG in North Sulawesi requires an adaptive approach that integrates national policy with local conditions through collaborative governance, logistics innovation, and technology-based accountability systems. Such an approach is expected to enhance the effectiveness of nutritional interventions while strengthening food security and promoting sustainable human resource development.